Qatar Foundation Annual Research Conference Proceedings Volume 2018 Issue 1 2018
DOI: 10.5339/qfarc.2018.eepd1033
|View full text |Cite
|
Sign up to set email alerts
|

Biomass distribution and soil characteristics along the distance from the coast in a natural mangrove forest in Qatar

Abstract: Mangrove is a woody plant which grows in intertidal zones. Mangrove forests are mainly distributed in subtropical and tropical regions, and are valuable for ecosystems and for society. Even in dry regions such as Qatar, mangrove forests provide ecosystem services despite their small area and low productivity compared with tropical mangroves. Carbon sequestration by mangroves is one of the main ecosystem services mitigating climate change, as mangrove forests are carbon-rich ecosystems. In mangrove forests, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
3
1
0
Order By: Relevance
“…Above ground carbon stocks AGC increased with increasing seaward distance, as has been reported in Qatar and Micronesia and in worldwide reviews [57,62]. However, the correlation between AGC and seaward distance was not significant, possibly due to the low number of plots or because of the lower AGC value in plot 3 which may have experienced greater exploitation pressure.…”
Section: Discussionsupporting
confidence: 59%
“…Above ground carbon stocks AGC increased with increasing seaward distance, as has been reported in Qatar and Micronesia and in worldwide reviews [57,62]. However, the correlation between AGC and seaward distance was not significant, possibly due to the low number of plots or because of the lower AGC value in plot 3 which may have experienced greater exploitation pressure.…”
Section: Discussionsupporting
confidence: 59%
“…Above ground carbon stocks AGC increased with increasing seaward distance, as has been reported in Qatar and Micronesia and in worldwide reviews (57,62). However, the correlation between AGC and seaward distance was not signi cant, possibly due to the low number of plots or because of the lower AGC value in plot 3 which may have experienced greater exploitation pressure.…”
Section: Discussionsupporting
confidence: 59%
“…Above ground carbon stocks AGC increased with increasing seaward distance, as has been reported in Qatar and Micronesia and in worldwide reviews (35,50). However, the correlation between AGC and seaward distance was not signi cant, possibly due to the low number of plots or because of the lower AGC value in plot 3 which may have experienced greater exploitation pressure.…”
Section: Discussionsupporting
confidence: 58%
“…Again, waterlogging or salinity, which affects decomposition rates, and therefore nutrients available for plant growth, might also explain some of these differences. In Qatar, Son et al (2018) (35) found that AGC increased as seaward distance increased.…”
Section: Introductionmentioning
confidence: 99%